2023
DOI: 10.1021/acscatal.2c04491
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Electrochemical Nitrogen Reduction on Molybdenum and Iron Carbides: Promising Catalysts or False Positives?

Abstract: The electrochemical dinitrogen reduction reaction (NRR) has recently gained much interest as it can potentially produce ammonia from renewable intermittent electricity and replace the Haber−Bosch process. Previous literature studies report Fe-and Mo-carbides as promising electrocatalysts for the NRR with activities higher than other metals. However, recent understanding of extraneous ammonia and nitrogen oxide contaminations have challenged previously published results. Here, we critically assess the NRR perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 79 publications
(193 reference statements)
1
16
0
Order By: Relevance
“…Izellar et al 22 critically assessed the ENRR activity of molybdenum and iron carbides, trying to reproduce peer-reviewed works that had reported a superior or excellent catalytic performance. 23,24 They found that the ammonia did not originate from the ENRR but from unavoidable extraneous ammonia and NOx impurities.…”
Section: Resultsmentioning
confidence: 99%
“…Izellar et al 22 critically assessed the ENRR activity of molybdenum and iron carbides, trying to reproduce peer-reviewed works that had reported a superior or excellent catalytic performance. 23,24 They found that the ammonia did not originate from the ENRR but from unavoidable extraneous ammonia and NOx impurities.…”
Section: Resultsmentioning
confidence: 99%
“…[12,56] This additional purification step was also applied to 15 N 2 (99 atom % 15 N, Sigma-Aldrich) used for isotope labelled experiments, as 15 N 2 might also contain traces of extraneous N species. [56,57]…”
Section: Methodsmentioning
confidence: 99%
“…Currently, industrial-scale NH 3 synthesis has mainly been achieved through the capital-and energy-intensive Haber-Bosch (H−B) approach 8 usually necessitating severe temperature (300−600 °C) and ultrahigh pressure (150−300 atm), 9 which is unsustainable and disadvantageous. 10 This process has a large carbon footprint, accounting for 1−2% of the global total energy consumption 11 and meanwhile discharging a large amount of greenhouse gas annually. 12 Considering such unwilling costs in energy and environment, it is highly desirable to find a cost-effective and sustainable technology to achieve highly efficient synthesis for N 2 reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Gaseous N 2 needs extremely large cleavage energy to fracture the strong NN triple bond due to its ultrahigh bonding strength, absence of permanent polarity, and low chemical activity resulting from the shared charges in π/2σ orbitals, which results in problematic NH 3 production at ambient conditions. Currently, industrial-scale NH 3 synthesis has mainly been achieved through the capital- and energy-intensive Haber-Bosch (H–B) approach usually necessitating severe temperature (300–600 °C) and ultrahigh pressure (150–300 atm), which is unsustainable and disadvantageous . This process has a large carbon footprint, accounting for 1–2% of the global total energy consumption and meanwhile discharging a large amount of greenhouse gas annually .…”
Section: Introductionmentioning
confidence: 99%